An ab-initio study of electronic and optical properties of RhXO3 (X = Ga, Ag) perovskites. (1st February 2022) - Rouf, Syed Awais; Hussain, Muhammad Iqbal; Mumtaz, Umair; Masood, Hafiz Tariq; Albalawi, Hind; Majeed, Abdul Mannan; Khalil, R M Arif; Mahmood, Q
Abstract: The ab-initio computations were performed to study the electronic and optoelectronic properties of RhXO 3 ( X = Ga, Ag ) perovskites using WIEN2k code. The RhGaO 3 has band gap of 2.29 eV, and the behavior of RhAgO 3 is metallic. The sub-TDOS of the studied materials revealed that rhodium and oxygen atoms have significant contributions in the valence band and conduction band formation of both materials. The silver cation is responsible for the reasonable peaks appearing at the Fermi level of RhAgO 3, which demonstrated the conducting nature of RhAgO 3 . The dielectric functions, optical conductivity, energy loss function, absorption coefficient, refractive index, extinction coefficient, and reflectivity are computed for these materials to understand the optical behavior of the studied materials. The analysis of optical properties ensure the RhGaO 3 is a promising material for optoelectronics while RhAgO 3 has metallic nature.